2015
DOI: 10.3390/ma8041752
|View full text |Cite
|
Sign up to set email alerts
|

Spherical V-Fe-MCM-48: The Synthesis, Characterization and Hydrothermal Stability

Abstract: Spherical MCM-48 mesoporous sieve co-doped with vanadium and iron was successfully synthesized via one-step hydrothermal method. The material was characterized by X-ray diffraction (XRD), nitrogen adsorption-desorption isotherms, inductively coupled plasma (ICP), scanning electron microscopy (SEM), transmission electron microscopy (TEM), diffuse reflectance UV-vis spectra, and X-ray photoelectron spectra (XPS) techniques. Results indicated that the V-Fe-MCM-48 showed an ordered 3D cubic mesostructure with sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Since iron and vanadium were introduced into the silica lattice, and the Pauling radius of Fe 3+ (0.64 Å) or V 4+ (0.58 Å) is greater than that of Si 4+ (0.42 Å), the lattice was caused to expand . It was confirmed that iron and vanadium were uniformly incorporated into the lattice . However, with the incorporation of iron and vanadium, the intensity of the diffraction peak decreases markedly, which results from the disorder of the mesoporous structure.…”
Section: Resultsmentioning
confidence: 97%
“…Since iron and vanadium were introduced into the silica lattice, and the Pauling radius of Fe 3+ (0.64 Å) or V 4+ (0.58 Å) is greater than that of Si 4+ (0.42 Å), the lattice was caused to expand . It was confirmed that iron and vanadium were uniformly incorporated into the lattice . However, with the incorporation of iron and vanadium, the intensity of the diffraction peak decreases markedly, which results from the disorder of the mesoporous structure.…”
Section: Resultsmentioning
confidence: 97%
“…Analysis of HR-TEM micrographs excluded presence of ordered structures typical for mesoporous silica systems like SBA or MCM [20,21] -Fig. 2.…”
Section: Resultsmentioning
confidence: 99%
“…Mesoporous silica is well-known for its advanced properties of high specific surface area, high porosity and well-defined pore system, which are ideal characteristics as molecules reaction zone [47][48][49][50]. Besides, due to the narrow pore size distribution, the growth of metal particles will be significantly limited in the confined channels.…”
Section: In the Mesoporous Channels Of Omssmentioning
confidence: 99%
“…To achieve this progress, many efforts have been put forward, including the direct hydrothermal method (DHT) [78,79], template ion-exchange method (TIE) [80], and wet impregnation method [81]. Particularly, in these methods, DHT is considered to be predominant due to its simplicity in the synthesis procedure, the controllable hydrolysis-condensation speed and high efficiency in incorporating the heteroatoms into the framework, while the rest are liable to induce the formation and aggregation of crystalline metal oxide on the surface of silica, causing the elution of metal active sites in the liquid-phase reactions [49,82]. However, the DHT method is restricted by the rigorous synthetic conditions, especially by pH value [83].…”
Section: In the Framework Of Omssmentioning
confidence: 99%
See 1 more Smart Citation